Design optimization of integrated rotor-less inductors for high-speed AC drive applications - Raza Khowja, Muhammad; Gerada, C.; Vakil, Gaurang; Patel, Chintanbai; Wheeler, Patrick (2017)
Discrete sub-system due to passive elements in motor drive require functional and structural integration to make efficient and power dense overall system. Such power dense system is the prerequisite in aerospace and marine applications. This paper presents the design optimization of integrated rotor-less inductors for high speed AC drive applications. Different slot-pole combinations are considered in this process. The single layer (SL) and double layer (DL) windings are chosen with concentrated winding (CW) and distributed winding (DW) configurations. The rotor-less inductors are optimized and compared in this paper with EE core inductor in terms of total losses, weight and AC copper resistance at both fundamental frequency and switching frequencies (10, 15 and 20 kHz). The comparative analysis between EE core and rotor-less inductors has shown a significant reduction in total losses and AC copper resistance at both fundamental frequency and all switching frequencies.